Is There a Role for Direct Oral Anticoagulants in the Primary and Secondary Prevention of Myeloproliferative Neoplasm Associated Thrombosis? - Uzma Faruqi; Karen A. Breen (Hemato, 2021)
Philadelphia chromosome negative myeloproliferative neoplasms (MPN) are clonal haematopoietic stem cell disorders. Of the MPNs, polycythaemia vera (PV) and essential thrombocythaemia (ET) confer a high thrombotic risk which may be the presenting feature of the disease. Thrombotic complications consist of both arterial and venous events and the presence of the JAK2 V617F mutation is associated with higher risk. Patients presenting with an unprovoked thrombus, particularly at an unusual site, e.g., splanchnic circulation, should be screened for the presence of this mutation. Historically, warfarin has been the only option for oral anticoagulation; however, there is now increasing evidence and practise to use direct oral anticoagulants (DOACs) in cancer. The seminal randomised control trials have demonstrated non-inferiority compared to low molecular weight heparin (LMWH) with a preferable bleeding profile. DOACs are now the first line treatment for atrial fibrillation and venous thromboembolic disease, as recommended by NICE, and therefore there is increasing familiarity with these agents. Furthermore, there are now targeted antidotes available. This paper reviews evidence for efficacy and safety of DOACs in MPN. Whilst no randomised control trials have been performed, several retrospective studies and reviews of registry data have reproducibly demonstrated that, alongside cytoreduction, DOACs represent an effective modality of anticoagulation for treatment of venous thromboembolism in MPN. Furthermore, dosing regimens provide the option for longer term secondary prophylaxis. Use of DOACs in arterial thrombosis is an area for future development and there is already some evidence for utility in peripheral vascular disease.